Adapting a pregnancy app (HealthyMoms) to support healthy habits in migrant women—a qualitative study on women's preferences and perceived needs to support health behaviors during pregnancy - Emmie Söderström; Christina Alexandrou; Sara Bressanutti; Johanna Sandborg; Anna-Karin Lindqvist; Marie Löf (Digital Health)
Background Healthy lifestyle behaviors in pregnancy are important for maternal and offspring health. Mobile health (mHealth) tools have potential to provide support for lifestyle behaviors at scale but such tools are commonly developed only in native languages, limiting reach in migrant populations. Objectives This qualitative study, in two of the largest migrant populations in Sweden (Arabic- and Somali-speaking women), aimed to explore (a) perceptions and needs of knowledge and support related to pregnancy and lifestyle behaviors and (b) needs of and attitudes towards a pregnancy app and how features and content in the app can be adapted to support healthier lifestyle behaviors in migrant women. Method Individual semi-structured interviews were conducted with Arabic ( n  = 10) and Somali-speaking women ( n  = 9). Data was analyzed using content analysis (inductive latent approach). Results Arabic- and Somali-speaking women described an increased need of knowledge regarding pregnancy and lifestyle behaviors. The social environment could both motivate behavior change and be a source of misinformation. Women expressed great trust in maternity healthcare but requested more information related to lifestyle behaviors. A pregnancy app was perceived as a helpful tool to support healthy lifestyle behaviors. Mere translations were suggested to be valuable, however, audio- and video-format to deliver content and inclusion of women's partners in the app were described as desirable adaptations. Conclusion Our findings can guide maternity healthcare on what support migrant women need and inform future development of mHealth tools for pregnant migrant populations. Future research should disentangle the degree of cultural adaptations required for mHealth lifestyle interventions provided by healthcare.